PERAN PEMERINTAH DAERAH DALAM PENGEMBANGAN OBYEK WISATA ISTANA SAYAP DI KABUPATEN PELALAWAN TAHUN 2009 -2011 - Syahfutra, Adi; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The tourism sector is a sector with the potential to be developed as a source of local revenue. Potential for tourism is expected to contribute to economic development. One of the cultural and historical heritage Pelalawan Riau Province is Istana Sayap Pelalawan kingdom. Istana Sayap in Pelalawan is evidence of the existence of the kingdom of historic relics Pelalawan the potential to do development.. This study was conducted to determine the role of local governments in developing heritage tourism Istana Sayap In Pelalawan Year 2009-2011. The main purpose of this study is to identify the role of local governments in managing the tourism aspect and area development Istana Sayap Pelalawan as a potential tourist areas. How to shape the role of local government and any regulatory or policy references only to support the development of this tourist area Istana Sayap that have higher contribution to local revenue. This includes research into the types of qualitative research using interview data collection technique is direct communication with the research informants and conduct a question and answer that related to the research problem. Selected object as the object of research is Pelalawan local government, particularly the agencies and units related work, which serves as an executive and in charge of the development task. Once identified, the results showed that the role of local government has not run optimally, there are obstacles that can not be resolved, such as the development of infrastructure has not teraplikasinya supporting infrastructure, yet effective promotional activities and quality of stakeholder managers still tend to be low, in making management.Keywords: Role of Local Government, Development, Istana Sayap Pelalawan